Biskop H. L. Martensen og Georg Brandes - Svenstrup, Thyge (Kirkehistoriske Samlinger, 1989)
Hans Lassen Martensen (1808-1884), Chaplain to the Royal Household, and from 1854 until his death the incumbent of the principal diocese in Denmark -the bishopric of Zealand. He and Georg Brandes (1842-1927), the prominent critic and cultural figure, acknowledged in the European sphere of literary criticism, were the two leading antagonists in the cultural debate that raged in Denmark during the 1870s, whereby the hegemony of the church over Danish intellectual life was ruptured under the influence of Brandes’ agitation. Both men, however, held a critical view of the consequences of economic liberalism on contemporary thought and social development; yet, on the question of the social, economic and political rights of the working class, Bishop Martensen is surprisingly enough more radical than Georg Brandes. Part One of Martensen’s Den christeiige Ethik, published in 1871 (German translation: Die christeliche Ethik the same year, and the English translation : Christian Ethics, 1873) claims attention through the relative autonomy which, in his book, the author allots to »modern humanity« and cultural evolution, which he sums up in the term emancipation: the liberation from the restraining barriers, false traditions and false authority which repress freedom. It is interesting, too, that precisely the same term is adopted by Brandes in his epochmaking work Hovedstrømninger i det 19de Aarhundredes Litteratur IVI, (German translation: Die Hauptströmungen der Literatur des neunzehnten Jahrhunderts; English translation: Main Currents in Nineteenth Century Literature). Likewise, Brandes’ conception of European historical development in the period 1789-1848, as a battle between the principle of freedom and that of authority, is seen as a secularised version of Martensen’s view of history, both are due to the influence of Hegel's philosophy. Inspired by the advance of the socialist movement in Denmark in the 1870s, Martensen published in 1874 a small book entitled Socialisme og Christendom (Socialism and Christianity), in which he takes up in complete sympathy descriptions by Ferd. Lassalle, Karl Marx (Das Kapital) and Fr. Engels (Die Lage der arbeitenden Klassen in England) of the conditions of industrial workers, and in which he launches a sharp attack on economic liberalism and the theory of free trade in Adam Smith's An Inquiry into the Nature and Causes ofthe Wealth ofNations (1776, Danish translation: 1779). And in the same book Martensen ultimately advocates far-reaching social reforms such as unemployment benefits, old-age pensions and health insurance, all suggestions which anticipate the social democratic welfare state. At the same time, in 1874-75, Georg Brandes published in Danish a long article by the German socialist leader Ferdinand Lassalle (German book edition 1877: Ferdinand Lassalle. Ein literarisches Charakterbild), which helped to introduce the theory of socialism into Denmark, but it did not actually contain proposals for reforms. Martensen’s final assessment of Brandes’ ideas was made in Part Three of his Christian ethics: Den sociale Ethik, 1878 (German translation: Die sociale Ethik the same year: English translation: Social Ethics 1882), in which he not only rejects John Stuart Mill's demand for the emancipation of women in The Subjection of Women, translated into Danish by Brandes the same year as the book was published (1869), but also in which, under the influence of anti-Semitic German writers, he attacks the »modern«, secularised Jews - who ought to be deprived of their civil rights because they cannot be expected as »aliens« and »unDanish« to be possessed of the same loyalty to the country as that of true Danes. Apart from this, the article comes to the conclusion that, as an elderly man, Bishop Martensen concerned himself in a qualified manner with the problems of a new epoch.